EFFECTIVE ASPECTS OF USING VIDEO MATERIALS IN ENGLISH LESSONS (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the effectiveness of using video materials in English language lessons. It discusses various methods for incorporating videos into the classroom, presents the results of research studies on their impact, and engages in a comprehensive discussion about their advantages and disadvantages. The article concludes with suggestions on how to optimize the use of video materials in English lessons.